The effects of preoperative nursing intervention of postoperative pain perception, pain behavior and compliance with bed exercises in Chiang Mai Hospital, Chiang Mai, Thailand. - Nunta Leksawasdi
This study investigated the problems: 1. Will preoperative nursing intervention: a. lessen pain perception? b. lessen non-verbal pain behavior? c. decrease patient's demand for postoperative analgesic? d. facilitate the patient's compliance to perform bed exercises among adult surgical patients within the 1st 8 postoperative hours? 2. Is there a relationship between the frequency of performing bed exercises and pain perception, non-verbal pain behavior levels, patient's demand for post-operative analgesics during the 1st 8 postoperative hours? 3. Is there a relationship between the frequency of performing bed exercises and patient's demand for postoperative analgesics during the 1st 48 postoperative hours? 4. Is there a relationship between the frequency of performing bed exercises and length of hospital stay? The following hypotheses were pose: 1. Preoperative nursing intervention given to the adult surgical patients will decrease pain perception and non-verbal pain behavior. 2. Adult surgical patients who perceived preoperative nursing intervention will decrease demand for postoperative analgesics. 3. Adult surgical patients trained with preoperative nursing intervention comply with bed exercises more frequently than those who do not receive similar nursing intervention. 4. There is a relationship between the frequency of performing bed exercises and pain perception, non-verbal pain behavior levels, patient's demand for post-operative analgesics during the 1st 8 postoperative hours. 5. There is a relationship between the frequency of performing bed exercises and patient's demand for postoperative analgesics during the 1st 48 postoperative hours. 6. There is a relationship between the frequency of performing bed exercises and length of hospital stay. The study gave the following results: 1. The adult surgical patients who received pre-operative nursing intervention significantly decreased pain perception and non-verbal pain behavior levels only at immediately after patients fully regained consciousness but not on the 4th and the 8th hour after patients fully regained consciousness. 2. Implementation of preoperative nursing intervention to the adult surgical patients prior to operation increased the ability of the patients to tolerate post-operative pain and significantly decreased pain behavior level in terms of patients' demand for postoperative analgesics. 3. The ability of patients to comply with bed exercises postoperatively was highly facilitated by the preoperative nursing intervention. 4. It was noted that the mean length of hospital stay was 1.70 days shorter for the adult surgical patients who received preoperative nursing intervention than those who did not receive similar nursing intervention. 5. Patients who turned from the 2nd to the 6th hour had significantly lesser pain perception and non-verbal pain behavior levels when observed at the 8th hour. 6. Patients who performed deep breathing and turning frequently had significantly lesser demand for analgesics during the 1st 48 postoperative hours. 7. Patients who performed frequently deep breathing and coughing had significantly shorter stay in the hospital.